On estimates of insider trading in sports betting - Karl Whelan (University College Dublin, UCD School of Economics, 2024)
Following the work of Shin (1993) and Cain, Law and Peel (1997, 2001), several researchers have reported estimates of the fraction of money placed on sports betting by "insiders" with superior information to bookmakers. We show the method for estimating the fraction of insiders used in this research is only accurate under highly unrealistic conditions and that these estimates will tend to be positive in realistic cases where there are no insiders. We also argue that variations in these estimates are unlikely to be related to variations in the amount of inside information but rather are more likely due to other factors such as variations in bookmakers' costs or the extent of competition in betting markets.
Keywords: G14; L83; Z20; 330; Sports Betting; Inside Information; Shin's z